Bioaccumulation of selenium in some organs of guinea pig - Morales, Millie Rose (Animo Repository, 1993)
Accumulation of selenium in the vital parts of the guinea pigs exposed to sublethal concentration of 3.25 mg/kg for seven days was determined using atomic absorption spectrophotometer. Eight organs were analyzed, namely the heart, kidney, liver, lungs, large intestines, small intestines, muscles and stomache. It was noted that selenium accumulated most in the liver. Guinea pigs exposed to 3.25 mg/kg selenium concentration showed the following mean values in mg/kg: liver (0.075) kidneys (0.069) small intestines (0.045) stomach (0.040) lungs (0.035) heart (0.025) large intestines (0.021) muscles (0.007).There were significant differences in concentration of selenium between control and experimental groups in the liver, kidneys, small intestines, stomach, lungs, heart and large intestine. Selenium levels in muscles did not differ significantly between control and treated groups.